Alburnus battalgilae, a synonym of A. attalus (Teleostei: Leuciscidae) - Bayçelebi̇ Esra; Turan, Davut; Kaya, Cüneyt; Freyhof, Jörg (Zootaxa, 2021)
Alburnus battalgilae Özuluğ & Freyhof, 2007 from the Gediz River drainage in western Anatolia is a junior synonym of A. attalus Özuluğ & Freyhof, 2007, from the adjacent Bakır River drainage. We were unable to confirm the morphological differences originally proposed. As both species have been described in the same publication, as First Reviewers, we prioritise of A. attalus over A. battalgilae.